Urgensi Bahasa Arab dalam Pendidikan Islam di Era Digital - Lilik (Ahad: Multidisciplinary Journal of Islamic Studies, 2025)
Arabic language learning holds a strategic position in Islamic education as it serves as the primary means for understanding foundational sources of Islamic teachings. This article employs a qualitative descriptive approach to illustrate the urgency of Arabic language learning within Islamic education amid digital transformation, while also identifying the emerging challenges and opportunities. Data were collected through literature review, exploration of academic sources, and thematic analysis of policy documents and previous studies. The findings indicate that the integration of technology into Arabic language learning can enhance learning accessibility, strengthen learners’ motivation, and develop communicative competence when supported by a well structured curriculum, appropriate instructional design, and adequate teacher training. Moreover, digitalization enables the use of multimedia content, digital libraries, and new spaces for interaction with native speakers or global Arabic-speaking communities.